Spatial spillover and threshold effect of green development efficiency on urban human settlement resilience in Yangtze River Delta urban agglomeration. - Zheng Wang; Xiaobo Xu; Jie Zhang (PLoS ONE, 2023)
Green development is the necessary path and fundamental way for urban development. Exploring the influence mechanism and spatial effect of green development on the urban human settlement resilience is conducive to promoting high-quality and sustainable urban development. We used the entropy method, super-efficient SBM model, spatial econometric model and threshold model to analyze the spatial spillover effect of green development efficiency on urban human settlement resilience and its nonlinear impact in the Yangtze River Delta(YRD) urban agglomeration. The results indicated that During the study period, the level of green development efficiency and urban settlement resilience was on the rise, and the spatial differences between different regions was significant. The green development efficiency of each city in the YRD urban agglomeration has a significant contribution to urban human settlement resilience in the region, but has a negative spatial effect on the level of urban human settlement resilience in the neighboring region. At different population density levels, the effect of green development efficiency on urban human settlement resilience shows a significant "V" non-linear characteristic. Furthermore, the influence of green development efficiency on urban human settlement resilience increases in a stepwise manner under different industrial structure distribution. The results of this study can help provide a reference basis for the creation of high-level, high-quality green and livable resilient cities in the YRD urban agglomeration under the concept of green development, and provide relevant experience for the construction of livable cities in other regions of China.